Demonstration and Testing of the Improved Shelterbelt Component in the Holos Model - Kröbel, Roland; Moore, Julius; Ni, Yu Zhao; McPherson, Aaron; Poppy, Laura; Soolanayakanahally, Raju Y.; Amichev, Beyhan Y.; Ward, Tricia; Laroque, Colin P.; Van Rees, Ken C. J.; Akhter, Fardausi (Frontiers in Environmental Science, 2020)
Using a participatory approach, the shelterbelt component of Canada’s whole-farm model Holos was upgraded from an age-determined to a circumference-determined (at breast height) calculation using a multi-stem averaging approach. The model interface was developed around the idea that a shelterbelt could have multiple rows, and a variable species composition within each row. With this, the model calculates the accumulated aboveground carbon in the standing biomass and a lookup table of modelled tree growth is used to add estimates of the belowground carbon. Going from an initial interface that asks for the current state, the model also incorporates an option of past and future shelterbelt plantings. In order to test the model’s suitability, we measured diverse shelterbelts (evergreen, deciduous, shrub type) in southern Saskatchewan, Canada representing commonly planted woody species. By making use of Caragana, Green Ash, Colorado Spruce, Siberian Elm, and a mixed Caragana/Green Ash tree rows, we tested how many tree circumference measurements would be required to yield a representative average. Later, these results were incorporated in the Holos model to calculate the accumulated above- and below-ground carbon in each shelterbelt type.